Livestock Building and Equipment Requirements - Jones, Rodney D.; Murphy, James P. (My University, 1999)
This publication describes the livestock building and equipment requirements for producers.
MF940_1999_10
Keywords: MF940; Equipment and Structures; Livestock; Economics; MF